Chemi-mechanical pulp from rapeseed straw - Potůček, František; Říhová, Martina; Gurung, Bijay (My University, 2016)
This study deals with chemi-mechanical pulping of rapeseed straw (species Brassica napus L. convar. napus). Three cold chemi-mechanical processes, namely neutral sulphite, alkaline sulphite, and caustic soda, were applied under laboratory conditions. The chemi-mechanical pulping comprises four main operations, viz. chipping, grinding, leaching, and beating. The influence of varying charges of chemicals on the total yield, strength properties such as bending stiffness, bending modulus of elasticity, curvature in the region of elastic and plastic deformation, as well as the tensile index of pulp hand sheets was determined. The results obtained revealed that the cold caustic soda pulping has greater effect on the bending stiffness and bending modulus of chemi-mechanical pulps in comparison with neutral sulphite and alkaline sulphite pulping, although the total pulp yield for caustic soda pulping was lower than that for neutral sulphite and alkaline sulphite pulping. For all three cold processes, the bending stiffness, as well as the bending modulus of elasticity in the region of elastic deformation increased with increasing the chemical charge. However, the tensile index of chemi-mechanical pulps was found to be significantly lower in comparison with kraft softwood pulp and pulp from waste paper. The chemi-mechanical pulp was characterized by its degree of polymerization which was measured in the range of 75 to 110 with respect to relatively great amount of low molecular substances presented in pulps prepared by the cold pulping process.
Chemicko-mechanická vláknina z řepkové slámy
Keywords: rapeseed straw; cold pulping process; pulp yield; bending stiffness; polymerization degree; řepková sláma; studený chemicko-mechanický postup; výtěžek vlákniny; pevnost v ohybu; stupeň polymerace